COVID-19 Pandemic- A Review of the Effects on the Environment - Selvina, Sandiawo; Ong, Ghim Hock; Cheng, Wan Hee; Wong, Ling Shing (INTI International University, 2021)
The scourge of the coronavirus diseases-2019 (COVID-19) has caused suffering to human population globally. It is one of the most devastating pandemic in history. With the current lockdown and restriction, there is a concern that this bleak period might spark an even more severe pollution and climate changes once this is over. This paper reviews the effects of post COVID-19 in the environmental perspective. Activities such as agriculture and urbanization has brought about the various input of pollutants into the natural ecosystem of Malaysia. In recent years it has been reported on the rise of the levels of harmful pollutants such as pesticides, heavy metals and hydrocarbons. Therefore, continuous monitoring and remediation researches has been carried out to curb the detrimental effects of pollutants in the natural environments of Malaysia. In this study, we discuss the status, impacts and sources of pollutions globally. It is hoped that the current review will provide a better picture of the current pollution status and to further aid to mitigate the pollution issues we are facing.